Commencement 2008 (Institutional Knowledge at Singapore Management University, 2008)
Chairman Ho Kwon Ping, Minister for Education Ng Eng Hen and President Howard Hunter at Commencement 2008. Singapore Management University celebrated its fifth commencement at Suntec City Convention Centre on 12 July 2008.